Defining the molecular features of radiation-induced glioma: A systematic review and meta-analysis. Issue 1 (12th August 2021) - Whitehouse, Jacqueline P; Howlett, Meegan; Federico, Aniello; Kool, Marcel; Endersby, Raelene; Gottardo, Nicholas G
Abstract: Background: Cranial radiation therapy is essential in treating many pediatric cancers, especially brain tumors; however, its use comes with the risk of developing second malignancies. Cranial radiation-induced gliomas (RIGs) are aggressive high-grade tumors with a dismal prognosis, for which no standard therapy exists. A definitive molecular signature for RIGs has not yet been established. We sought to address this gap by performing a systematic review and meta-analysis of the molecular features of cranial RIGs. Methods: A systematic review of the literature was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Articles and case reports that described molecular analyses of cranial radiation-induced high-grade gliomas were identified and evaluated, and data extracted for collation. Results: Of 1727 records identified, 31 were eligible, containing 102 unique RIGs with molecular data. The most frequent genetic alterations in RIGs included PDGFRA or TP53 mutations, PDGFRA or CDK4 amplifications, and CDKN2A deletion, along with 1q gain, 1p loss and 13q loss. Of note, mutations in ACVR1, EGFR, H3F3A, HIST1H3B, HIST1H3C, IDH2, SMARCB1 or the TERT promoter were not observed. A comparative analysis revealed that RIGs are molecularly distinct from most other astrocytomas and gliomas and instead align most closely with the pedGBM_RTK1 subgroup of pediatric glioblastoma. Conclusions: This comprehensive analysis highlights the major molecular features of RIGs, demonstrates their molecular distinction from many other astrocytomas and gliomas, and reveals potential genetic drivers and therapeutic targets for this currently fatal disease.